Stato-nazione, binomio in crisi? - Baglioni, Lorenzo Grifone (SocietàMutamentoPolitica, 2011)
The nation-state, as institution and community, seems to characterize the social dynamics of the modern age. Yet, it appears to interact with increasing difficulty with the macro-processes of the contemporary world (globalization and individualization) reducing the scope of its possible policies. The nation-state appears today to be in crisis as a social organization which, magnified by methodological nationalism, gives an institutional form to nation by calling upon its monopoly of law and morality on which are founded its sovereignty and its legitimacy. The crisis of this ‘marriage’ of state and nation shows three levels (transnationalization, devolution and privatization) and is marked by two emergency areas (systemic and individual) that the paper explores focusing on territoriality and citizenship.